2016
DOI: 10.1002/ejsp.2234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diversity versus segregation on automatic approach and avoidance behavior towards own and other ethnic groups

Abstract: We present the results of a study in which we measured automatic intergroup behavior and evaluations in ethnic majority and minority group members. We focus our attention on the level of segregation and diversity of immediate life contexts as indicators of outgroup exposure. Specifically, Dutch ethnic minority and majority students enrolled at ethnically segregated and diverse schools completed a measure of automatic approach and avoidance behavior and reported explicit intergroup attitudes. The research is fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…In the case of our present focus on approach/avoidance tasks as indirect attitude measures, this result is to be linked with two recent experiments published after we conducted our research. A first experiment compared students from segregated versus non‐segregated schools by using the Manikin task (Degner et al, ). In this experiment, minority students from segregated schools (i.e., from schools with a majority of students from immigration background) displayed a pro‐ingroup compatibility effect, whereas minority students from non‐segregated schools (i.e., from schools with a majority of white students) displayed a pro‐outgroup compatibility effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of our present focus on approach/avoidance tasks as indirect attitude measures, this result is to be linked with two recent experiments published after we conducted our research. A first experiment compared students from segregated versus non‐segregated schools by using the Manikin task (Degner et al, ). In this experiment, minority students from segregated schools (i.e., from schools with a majority of students from immigration background) displayed a pro‐ingroup compatibility effect, whereas minority students from non‐segregated schools (i.e., from schools with a majority of white students) displayed a pro‐outgroup compatibility effect.…”
Section: Discussionmentioning
confidence: 99%
“…We were also interested in whether this variability was linked with self‐reported prejudice toward the outgroup (here, North African individuals). To our knowledge, two studies were able to show a link between intergroup approach/avoidance effects and self‐reported prejudice (Clow & Olson, ; Degner et al, ), but such a link is not always observed (Neumann et al, ).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Findings regarding stigmatized group members' intergroup evaluations on implicit measures vary greatly, and different studies have documented ingroup favoritism, outgroup favoritism, or no group preferences (Axt, Ebersole, & Nosek, 2014;Degner, Essien, & Reichardt, 2016;Essien et al, 2020;Rae, Newheiser, & Olson, 2015;Rudman et al, 2002). Thus far, these variations in intergroup evaluations have not been exhaustively explained.…”
Section: G Roup E Valuati On S a S A Manife S Tati On Of S Elf-g Romentioning
confidence: 99%